Patients' expectations for and experiences with primary healthcare services received from a patient centered medical home. Issue 6 (June 2020) - Reis, Janet; Juker, Dawn; Volk, Molly; Stevenson, Chelsea
Highlights: Patients, in their own words, prioritize patient-centered care. Personal responsibility for health, reciprocal listening, asking questions are key. Patients seek help with changes in diet and in exercise. Patients face many and varied challenges to taking care of their health. Primary care clinics require broader partnerships to address patients' needs. Abstract: Objective: Expectations for and experiences with healthcare services are summarized for 1143 patients receiving care in a statewide demonstration of Patient Centered Medical Homes (PCMH). Methods: Patients were recruited from 91 primary care clinics for semi-structured interviews to determine what patients expect, what they plan to do and how they intend to execute their plans in partnership with their healthcare team. Results: The majority (78%) of patients defined the patient-team partnership as a collaborative and problem-solving effort. Overall, 68% defined responsibility for own health as a personal responsibility; 55% defined listening to patient's concerns and answering questions as a responsibility of their healthcare team. Diet and exercise came up most frequently whether as a personal responsibility, issues for receiving additional help from their clinic, or plans for personal change. Conclusion: Patients' preferred a collaborative, problem-solving healthcare team partnership but also had boundaries for what additional services they wanted from this team. Practice Implications: Patients' expectations for a collaborative partnership, acceptance of personal responsibility and interest in diet and exercise expands opportunities for patient education and teamwork. Clinics' engagement with broader resources would be needed to address patients' many and varied challenges to taking care of their health.